Risk factors and comorbidity of ICD‐11 PTSD and complex PTSD: Findings from a trauma‐exposed population based sample of adults in the United Kingdom - Karatzias, Thanos; Hyland, Philip; Bradley, Aoife; Cloitre, Marylène; Roberts, Neil P.; Bisson, Jonathan I.; Shevlin, Mark (Depression and anxiety, 2019)
Background Following the recently published 11th version of the WHO International Classification of Diseases (ICD‐11), we sought to examine the risk factors and comorbidities associated with posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD). Method Cross‐sectional and retrospective design. The sample consisted of 1,051 trauma‐exposed participants from a nationally representative panel of the UK adult population. Results A total of 5.3% (95% confidence interval [CI] = 4.0–6.7%) met the diagnostic criteria for PTSD and 12.9% (95% CI = 10.9–15.0%) for CPTSD. Diagnosis of PTSD was independently associated with being female, being in a relationship, and the recency of traumatic exposure. CPTSD was independently associated with younger age, interpersonal trauma in childhood, and interpersonal trauma in adulthood. Growing up in an urban environment was associated with the diagnosis of PTSD and CPTSD. High rates of physical and mental health comorbidity were observed for PTSD and CPTSD. Those with CPTSD were more likely to endorse symptoms reflecting major depressive disorder (odds ratio [OR] = 21.85, 95 CI = 12.51–38.04) and generalized anxiety disorder (OR = 24.63, 95 CI = 14.77–41.07). Presence of PTSD (OR = 3.13, 95 CI = 1.81–5.41) and CPTSD (OR = 3.43, 95 CI = 2.37–4.70) increased the likelihood of suicidality by more than three times. Nearly half the participants with PTSD and CPTSD reported the presence of a chronic illness. Conclusions CPTSD is a more common, comorbid, debilitating condition compared to PTSD. Further research is now required to identify effective interventions for its treatment.